THE ROLE OF LEADERSHIP SKILLS IN ENHANCING LANGUAGE TEACHING EFFECTIVENESS AMONG YOUTH - Risvayeva Charos Zaydilla qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. Leadership skills play a crucial role in improving the effectiveness of language teaching among youth. In modern educational contexts, teachers are not only knowledge transmitters but also leaders who inspire, guide, and motivate learners. This article explores how leadership qualities such as communication, adaptability, emotional intelligence, and decision-making contribute to better language learning outcomes. By fostering a supportive and engaging classroom environment, educators with strong leadership skills can enhance student participation, confidence, and overall language proficiency. The study highlights the importance of integrating leadership development into teacher training programs to meet the evolving needs of young learners in a globalized world.